Alunos com deficiência visual e suas relações interpessoais no processo de inclusão escolar - Tezori, Rosangela Cristina Sales (2015)
It is denominated Visual Impairment (VI) the spectrum that goes from blindness to low vision. In low vision, there is an alteration of the functional capacity due to factors like significant lowered visual acuity, important reduction of the visual field and of the contrasts sensibility and the limitation of other abilities. In blindness, there is total vision loss, even the absence of light projection. Among the difficulties, that a visually impaired person has to deal with, is the engagement and permanency in school, in which, aside the physical-environmental adaptation, the interpersonal relations are also established with teachers and peers that have the capacity to see. Due to this context, the research had as its objective, identify the interpersonal relations that are established between students with VI and the teachers, peers and other individuals that are part of the student‟s school environment. The research is characterized as exploratory in the qualitative approach. Participated in the research, three students with VI (blindness and low vision) enrolled in the primary education (Ensino Fundamental Ciclo II). The data was obtained by observation means of the interaction of the students in class-time and during break and from semi-structured interviews with them. The data was analyzed in the light of theoretical reference, which was base for this research. The results showed the difficulties addressed by the students with VI in the sense of conquering the feeling of belonging to a group of friends; being able to follow the content taught; difficulty from these students to engage their peers and teachers. The results contemplated the traced objectives in this research in the sense that it was possible to know how the interpersonal relations were established, by the students with VI, allowing them the opportunity to express their opinions and feelings on the school environment. It seems necessary to have a warm-hearted hospitality, considering that the students carry with them experiences and feelings from their home and transfer them to their teachers and peers. As important as the care with content and academic objectives given to students, there should be a meticulous attention given to the form of how the interpersonal relations are established in the school context, since these are valuable elements for the development of the student in all his/her totality.